Epidemiology, rehabilitation and prevention of ankle sprains in basketball players - Lewandowska, Anna; Ratuszek-Sadowska, Dorota; Hoffman, Jarosław; Hoffman, Anetta; Kuczma, Monika; Rojek, Johanna; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Basketball is a sports discipline in which the ankle sprain is the most common injury. It is considered to be an aggravated activity by its dimension of teamwork, contact and requiring a variety of motion dynamics. The aim of this paper is to identify basketball game elements that contribute to the development of traumatic torsion injuries, to present methods of injury prevention and to present possible methods for the rehabilitation of athletes in different stages of injury healing. A sprain and a torsion of the ankle is not a traumatic event defined at one time, but is often a cycle of repetitive trauma. It is also important to educate competitors not to underestimate these types of injuries and to treat them with serious medical and rehabilitation procedures. Rehabilitation of the ankle joint is dependent on the degree of injury, and above all on the extent of the damaged tissue. In order to avoid trauma, proprioception and global stabilization training play a very important role. Unstable ankle instability is associated with serious complications.